Использование в производстве автоклавного ячеистого бетона модифицирующих добавок, обеспечивающих ресурсосбережение и повышение качества готовой продукции - Сенатова, К. С.; Олецкая, Л. П.; Фоменок, И. И.; Чернякевич, Л. А. (БНТУ, 2020)
In this work, the additive S-DrillTMCL grade A produced by SOOO Synergikom was investigated; "Stachement 2000M" produced by JLLC "Stakhema-M". The obtained research results indicate the advisability of using modifying additives in the technology of autoclaved aerated concrete. The results of industrial tests have shown the effectiveness of their use in order to save resources and improve the physical and mechanical properties of aerated concrete building blocks.